Framing the environmental humanities - Bergthaller, Hannes; Mortensen, Peter Bjerre (Studies in environmental humanities ;, 2018)
"The concept of framing has long intrigued and troubled scholars in fields including philosophy, rhetoric, media studies and literary criticism. But framing also has rich implications for the environmental debate, urging us to reconsider how we understand the relationship between humans and their ecological environment, culture and nature. The contributors to this wide-ranging volume use the concept of framing to engage with key questions in environmental literature, history, politics, film, tv, and pedagogy. In so doing, they show that framing can serve as a valuable analytical tool connecting different academic discourses within the emergent interdisciplinary field of environmental humanities. No less importantly, they demonstrate how increased awareness of framing strategies and framing effects can help us move society in a more sustainable direction"--